A case report of recurrent hypokalaemic periodic paralysis in a young male patient - Pulin Gupta; Vikas T Talreja; M S Dhananjaya; Sakshi Mittal (The Egyptian Journal of Internal Medicine, 2015)
A 21-year-old normotensive male patient presented with acute-onset flaccid paralysis with the history of a similar episode a few months back. Clinical and laboratory evaluation revealed lower motor neuron type of flaccid quadriparesis with hypokalaemia, normal anion gap metabolic acidosis, bicarbonaturia and transtubular potassium concentration gradient more than 7. Subsequently, urine acidification test (by ammonium chloride challenge test) was performed and diagnosis of renal tubular acidosis was established. The patient ultrasound did not show nephrocalcinosis, and history of recurrent diarrhoea preceding the attack revealed that the patient also had coeliac disease. The patient responded to conservative management (Sohl′s solution) and gluten-free diet.